Ljudska pesem iz Prekmurja kot dejavnik ohranjanja slovenščine v Torontu - Kralj, Tadej (Glasnik Slovenskega etnološkega društva, 2020)
This article represents the role of folk song from Prekmurje as one of the factors to preserve Slovene language in Slovene community in Toronto in the 1950s and 1960s. The role of Slovene language as the heritage language was seen in communication and in symbolic level. The analysis of folk songs from the legacy of dr. France Cigan is based on the intertextual comparison of variants of folk songs from Prekmurje and shows the differences between them. While reproducting they were spontaneously using intertextual references and preserving language constituents on fonetic, lexical and morfhological level of language.
Keywords: dediščinski jezik; folk song; heritage language; ljudska pesem; Prekmurje; Slovene community; Slovene language; slovenska skupnost; slovenski jezik; Toronto